Utilization Of Productive Zakat Through The Indonesian Primary Agroative Producers Cooperative (KPAPI) In The Development Of Horticulture Agriculture - Maulana, Riki; Cahya Komala, Neng; Maulana, Sahrul; Istiqamah, Nimatul (ASAS, 2026)
Community welfare is one of the main objectives of the Unitary State of the Republic of Indonesia as stated in the Preamble to the 1945 Constitution. Zakat as an Islamic economic instrument has strategic potential to support economic and social development, particularly through productive zakat. However, the utilization of zakat in Indonesia is not optimal due to low public literacy, weak management of nadzir, and lack of government support. This study aims to explore the potential of productive zakat in supporting community economic empowerment, with a focus on the development of halal tourism. This study uses a qualitative approach through a case analysis of the management of Land of Zakat Teras Lembang managed by the Sinergi Foundation. The research method used is a qualitative methodology and an empirical legal approach, is to determine how zakat is implemented in zakat administration from the perspective of Islamic economic law. The results show that zakat management through nadzir innovation with a business model based on Mudharabah and Ijarah contracts can increase the economic and social value of the surrounding community. Productive zakat contributes to the growth of Micro, Small, and Medium Enterprises (MSMEs), the provision of employment, the development of halal tourism infrastructure, and increased regional income. Furthermore, the integration of zakat with halal tourism creates a sustainable development model aligned with Sharia principles, encompassing spiritual, social, economic, and environmental aspects. This study recommends the importance of collaboration between nadzir (managers), the government, the private sector, and the community to strengthen transparent, professional, and technology based productive zakat governance. These findings are expected to serve as a reference in formulating more effective zakat management policies and strategies to promote community welfare and Sharia-based economic growth.